Figurative Language in Rabab Pasisia Oral Literature and Its Implications on the Develompment of Figuratives of Speech Teaching Materials - Handayani, Dina Fitria (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2024)
Figurative language is a form of language that is often used in oral literature. One example of oral literature that uses figurative language is Rabab Pasisia. Rabab Pasisia is a type of oral literature originating from Minangkabau, West Sumatera. This study aims to analyze the use of figurative language in the oral literature of Rabab Pasisia and its implications for the preparation of figurative language teaching materials. The method used is a qualitative analysis of textual data from the oral literature of Rabab Pasisia. The data were analyzed by identifying the types of figurative language used in the literature. The results of the study show that figurative language in Rabab Pasisia includes the use of figures of speech such as simile, personification, alliteration, ellipsis, hyperbole, antithesis, metaphor. The use of this figurative language gives aesthetic value to Rabab Pasisia's oral literature and makes it more lively and interesting. The implication of this research is that figurative language in Rabab Pasisia can be an interesting teaching material in teaching figurative language. Teaching materials about figure of speech can be arranged by paying attention to the use of figurative language in Rabab Pasisia. This can help students to understand the concept of figure of speech better and develop their creativity in using figurative language in their own literary works.